Game Karapan Sapi - Nanda Aditya Widhisyah Putra; Andiani, Andiani; Adi Wahyu Pribadi (Prosiding SISFOTEK, 2023)
Nowadays, many children use Android via mobile phone devices that are played relatively quickly. In fact, it is not uncommon for the activity of playing this game to cause an addiction to continue playing the game, therefore educational alphabet games are beneficial to develop, especially for children. who is already addicted to Android. On the other hand, games function as a means of education. Android addiction often makes players forget many things and focus on the devices that support them in playing the game. One of the things they forget is culture, some of them who are familiar with games using modern technology tend to ignore games that have domestic cultural values.